Training and Development Model for Higher Education Institution in the Context of Lao P.D.R - Shahren, Ahmad Zaidi Adruce; Zaimuariffudin Shukri, Nordin; Khanthaly, Sae Phimmasenh (Microthink Institute, 2017)
In the constantly changing environment, organizations have to find ways to maintain their competitive advantage. Training and development model for higher learning institution is one of the ways in which organization can find its competitive advantage because university lecturers being trained have more diverse set of knowledge and skills that will help to support the organization growth. This research tries to find out the suitable model for training of personnel. Initially, a detailed review about challenges to higher education in the context of Lao P.D.R in this matter is presented and then the research introduces a framework of a proposed model of personnel training in a higher learning institution.